Glyceraldehyde-3-Phosphate Dehydrogenase Binds with Spike Protein and Inhibits the Entry of SARS-CoV-2 into Host Cells - Rahul Dilawari; Gaurav Kumar Chaubey; Radheshyam Modanwal; Asmita Dhiman; Sharmila Talukdar; Ajay Kumar; Chaaya Iyengar Raje; Manoj Raje (Karger Publishers, 2024)
Introduction: Coronavirus disease 2019 caused by coronavirus-2 (SARS-CoV-2) has emerged as an aggressive viral pandemic. Health care providers confront a challenging task for rapid development of effective strategies to combat this and its long-term after effects. Virus entry into host cells involves interaction between receptor-binding domain (RBD) of spike (S) protein S1 subunit with angiotensin converting enzyme present on host cells. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a moonlighting enzyme involved in cellular glycolytic energy metabolism and micronutrient homeostasis. It is deployed in various cellular compartments and the extra cellular milieu. Though it is known to moonlight as a component of mammalian innate immune defense machinery, till date its role in viral restriction remains unknown. Method: Recombinant S protein, the RBD, and human GAPDH protein were used for solid phase binding assays and biolayer interferometry. Pseudovirus particles expressing four different strain variants of S protein all harboring ZsGreen gene as marker of infection were used for flow cytometry-based infectivity assays. Results: Pseudovirus entry into target cells in culture was significantly inhibited by addition of human GAPDH into the extracellular medium. Binding assays demonstrated that human GAPDH binds to S protein and RBD of SARS-CoV-2 with nanomolar affinity. Conclusions: Our investigations suggest that this interaction of GAPDH interferes in the viral docking with hACE2 receptors, thereby affecting viral ingress into mammalian cells.